Pengaruh Struktur Modal Terhadap Profitabilitas Perusahaan Manufaktur Tahun 2019-2022 - Sabakodi, Marijka Yuliantini; Andreas, Hans Hananto (Owner : Riset dan Jurnal Akuntansi, 2024)
Capital structure and profitability are essential factors in business, where profitability serves as the primary indicator of a company's success. This research aims to examine the impact of capital structure on profitability in manufacturing companies before and after the COVID-19 pandemic, focusing on companies listed on the Indonesia Stock Exchange (IDX). The research methodology employed multiple linear regression analysis. The F-test results indicate an F-value of 53.817 with a significance level (P-value) of 0.000, which is smaller than ? = 0.05, indicating the suitability of the model used in this study. The adjusted R-squared (adjusted coefficient of determination) is 0.571. The t-test calculations show that the regression coefficient (X1) for Debt to Equity Ratio (DER) is 0.248, which is positively valued, with a significance level of 0.008, less than 0.050. The two-tailed P-value for the difference between ROA (Return on Assets) Before Pandemic and ROA After Pandemic is 0.110, which is greater than 0.05. Similarly, the two-tailed P-value for the difference between DER Before Pandemic and DER After Pandemic is 0.929, also greater than 0.05. In conclusion, Debt to Equity Ratio (DER) has a significantly positive impact on Profitability. Based on the ROA ratio, there is no significant difference in profitability (ROA) among Manufacturing Companies on the Indonesia Stock Exchange before and after the COVID-19 pandemic. Additionally, based on the DER ratio, there is no significant difference in the Debt to Equity Ratio (DER) among Manufacturing Companies on the Indonesia Stock Exchange before and after the COVID-19 pandemic.